Spatio-temporal variability of leaf macronutrients in a conilon coffee crop - Cezana, Diego Capucho; Gontijo, Ivoney; Cavalcanti, André Cayô; Silva, Marcelo Barreto da; Santos, Eduardo Oliveira de Jesus; Partelli, Fábio Luiz (Brazilian Journal of Production Engineering, 2024)
Studies focusing the understanding of spatio-temporal variability of soil and plant attributes may contribute to the rational use of agricultural inputs, enabling economic and environmental profits. The objective of this work was to determine the spatial and temporal variability of the foliar macronutrients in a Coffea canephora (Conilon coffee) plantation, in two sampling periods (pre-harvest and fruit growth). The study was performed in a Conilon coffee plantation with double spacing of 3.0 x 2.0 x 1.0m (4.000 plat ha-1) under drip irrigation system, in the county of São Mateus, Espírito Santo - Brazil. An irregular mesh with approximately 1.37 ha with 100 points, at a minimum distance of 2 m with each other, was installed. On each sampling point foliar tissue samples were collected in two distinctive periods, during pre-harvest and fruit growth and the levels of foliar macronutrients were determined. Results were submitted to descriptive analysis and geostatistics. A moderate spatial dependence structure was observed and verified for foliar contents of nitrogen, phosphorus, potassium and calcium in both sampling periods.
Keywords: Semivariogram; kriging; precision agriculture; Coffea canephora